Qualitative and quantitative analysis methods for quality control of rhubarb in Taiwan’s markets - Au, Thanh-Thuy-Dung; Ho, Yu-Ling; Chang, Yuan-Shiun (Frontiers in Pharmacology, 2024)
Introduction: Rhubarb is a Traditional Chinese Medicine (TCM) used to release heat and has cathartic effects. The official Rhubarb in Taiwan Herbal Pharmacopeias 4th edition (THP 4th) and China Pharmacopeia 2020 (CP2020) are the roots and rhizomes of Rheum palmatum L. and Rheum tanguticum Maxim. ex Balf., and Rheum officinale Baill. However, the Rheum genus is a large genus with many different species, and owing to the similarity in appearance and taste with official rhubarb, there needs to be more clarity in the distinction between the species of rhubarb and their applications. Given the time-consuming and complicated extraction and chromatography methods outlined in Pharmacopeias, we improved the qualitative and quantitative analysis methods for rhubarb in the market. Hence, we applied our method to identify the species and quality of official and unofficial rhubarb. Method: We analyzed 21 rhubarb samples from the Taiwanese market using a proposed HPLC-based extraction and qualitative analysis employing eight markers: aloe-emodin, rhein, emodin, chrysophanol, physcion, rhapontigenin, rhaponticin, and resveratrol. Additionally, we developed a TLC method for the analysis of rhubarb. KEGG pathway analysis was used to clarify the phytochemical and pharmacological knowledge of official and unofficial rhubarb. Results: Rhein and rhapontigenin emerged as key markers to differentiate official and unofficial Rhubarb. Rhapontigenin is abundant in unofficial rhubarb; however, rhein content was low. In contrast, their contents in official rhubarb were opposite to that of unofficial. TLC analysis used rhein and rhapontigenin to identify Rhubarb in Taiwan’s markets, whereas KEGG pathway analysis revealed that anthraquinones and stilbenes affected different pathways. Discussion: This study used eight reference standards to propose a quality control method for rhubarb in Taiwanese markets. We propose a rapid extraction method and quantitative analysis of rhubarb to differentiate between official and unofficial rhubarb.